Pengaruh Budaya Organisasi dan Kepemimpinan Kepala Sekolah Terhadap Prestasi Kerja Guru pada SMP Unggul Calang Kabupaten Aceh Jaya - Husna, Asmaul (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research was conducted to determine the effect of organizational culture and principal leadership on teacher performance at Unggul Calang Middle School, Krueng Sabee District, Aceh Jaya Regency. This research is located at Unggul Calang Middle School. The population in this study were all teachers at Unggul Calang Middle School, Krueng Sabee District, Aceh Jaya Regency, namely 6 people, while the samples in this study were 5 teachers. The sampling method that the authors use is purposive sampling method. This study uses qualitative methods by using hypotheses and then conducting field tests. To analyze the respondent's level of agreement, it is measured using a Likert scale. The results of the study found that organizational culture and leadership variables had an effect on work performance. This can be proven from the average percentage of respondents who answered agree + strongly agreed, which was 78.66%, which was 78.66% greater than those who answered strongly disagree + disagree, which was 10.67%, where S + SS > STS + TS. Then the hypothesis can be accepted